Ethics in psychosocial and biomedical research – A training experience at the Interdisciplinary Center for Bioethics (CIEB) of the University of Chile - Lolas Stepke, Fernando; Rodriguez, Eduardo (Acta Bioethica, 2012)
This paper reviews the experience in training Latin American professionals and scientists in the ethics of biomedical and psychosocial research at the Interdisciplinary Center for Studies in Bioethics (CIEB) of the University of Chile, aided by a grant from Fogarty International Center (FIC) – National Institutes of Health from 2002 to 2011. In these 10 years of experience, 50 trainees have completed a 12-month training combining on-line and in-person teaching and learning activities, with further support for maintaining contact via webmail and personal meetings. The network formed by faculty and former trainees has published extensively on issues relevant in the continent and has been instrumental in promoting new master level courses at different universities, drafting regulations and norms, and promoting the use of bioethical discourse in health care and research. Evaluation meetings have shown that while most trainees did benefit from the experience and contributed highly to developments at their home institutions and countries, some degree of structuring of demand for qualified personnel is needed in order to better utilize the human resources created by the program. Publications and otherdeliverables of trainees and faculty are presented.